2015
DOI: 10.1093/mnras/stv1578
|View full text |Cite
|
Sign up to set email alerts
|

Intergalactic magnetogenesis at Cosmic Dawn by photoionization

Abstract: We present a detailed analysis of an astrophysical mechanism that generates cosmological magnetic fields during the Epoch of Reionization. It is based on the photoionization of the Intergalactic Medium by the first sources formed in the Universe. First the induction equation is derived, then the characteristic length and time scales of the mechanism are identified, and finally numerical applications are carried out for first stars, primordial galaxies and distant powerful quasars. In these simple examples, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 44 publications
(47 reference statements)
1
41
0
Order By: Relevance
“…However, recent analyses of the γ-ray spectra of distant blazars suggest the presence of a magnetic field exceeding 10 −18 − 10 −15 G in cosmic voids [15][16][17] where the turbulent dynamo is unlikely to operate. The only viable astrophysical mechanism for the generation of such fields is based on return currents induced by cosmic-rays escaping from young galaxies and streaming in the high resistivity, non-uniform intergalactic plasma, just prior to reionisation [18][19][20]. This mechanism cannot however generate a field stronger than ∼ 10 −17 − 10 −16 G, while the rather * Corresponding author: gianluca.gregori@physics.ox.ac.uk conservative lower limit of 10 −18 G from current blazar observations [21] is likely to improve significantly when the Cherenkov Telescope Array begins operations [22].…”
mentioning
confidence: 99%
“…However, recent analyses of the γ-ray spectra of distant blazars suggest the presence of a magnetic field exceeding 10 −18 − 10 −15 G in cosmic voids [15][16][17] where the turbulent dynamo is unlikely to operate. The only viable astrophysical mechanism for the generation of such fields is based on return currents induced by cosmic-rays escaping from young galaxies and streaming in the high resistivity, non-uniform intergalactic plasma, just prior to reionisation [18][19][20]. This mechanism cannot however generate a field stronger than ∼ 10 −17 − 10 −16 G, while the rather * Corresponding author: gianluca.gregori@physics.ox.ac.uk conservative lower limit of 10 −18 G from current blazar observations [21] is likely to improve significantly when the Cherenkov Telescope Array begins operations [22].…”
mentioning
confidence: 99%
“…Anisotropic UV radiation fields are naturally realized in this epoch because neutral hydrogen clouds can absorb UV photons effectively, and therefore the magnetic fields are mostly generated behind the clouds (Langer et al 2005;Ando et al 2010). In cosmological timescale, the force of pressure gradient caused by UV photons from first-generation stars as well as CRs from supernovae explosions are balanced with the force of electric fields induced by the charge separation, and so the rotation component of those fields induces magnetic fields (Langer et al 2003;Chuzhoy 2004;Langer et al 2005;Ando et al 2010;Miniati & Bell 2011;Shiromoto et al 2014;Durrive & Langer 2015). The field amplitude through these mechanisms in the IGM ranges from ∼ 10 −19 G to ∼ 10 −16 G, depending on the model parameters.…”
Section: Epoch Of Reionizationmentioning
confidence: 99%
“…Stronger fields can be locally expected near luminous sources. Based on radiation hydrodynamics simulations of proto-first-star formation, Durrive & Langer (2015) found that ∼ 10 −9 G fields are generated on the surface of the accretion disk around a protofirst-star. These fields would be blown out from the disk and diffuse into the low density regions, which may affect the next generation star formation activities (Durrive & Langer 2015).…”
Section: Epoch Of Reionizationmentioning
confidence: 99%
“…Magnetic fields of strengths of the order of ∼ 10 −16 G are thought to be present in the voids between galaxy clusters; see for the pioneering work and Durrer & Neronov (2013) for a review and references therein. These are thought to be the result of seed magnetic field amplification, with two scenarios of the origin currently under discussion; see for a review: a bottom-up (astrophysical) scenario, where the seed is typically very weak and magnetic field is transferred from local sources within galaxies to larger scales, and a top-down (cosmological) scenario where a magnetic field is generated prior to galaxy formation in the early universe on scales that are large at the present epoch.…”
Section: Introductionmentioning
confidence: 99%